Analisis Faktor-Faktor yang Mempengaruhi Willingness to Pay pada Pelanggan Restoran Pizza - Handayani, Fitri; Ahmadi, Alyssa Putri; Zalma, Sucika Putri; Ulandari, Ayu; Suhud, Usep (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2020)
Abstract: This study aims to improve the factors that influence the willingness to pay to pizza restaurant customers. In this case, there are four variables used to measure, namely consumer knowledge, service quality, social media marketing and attitude. Data collection was carried out in Jakarta during the PSBB (Large-Scale Social Limitation) period from April to May 2020. Data were collected using a bold questionnaire and respondents were selected using convenience sampling techniques. Total respondents in this study amounted to 250 people consisting of 76 men and 174 women who had recommended a pizza restaurant. Data were processed using exploratory factor analysis and structural equation models. The results showed the variable consumer knowledge of positive and significant attitudes. Variables of consumer knowledge, service quality, social media marketing and attitudes affect the willingness to pay positively and significantly. So, it can be concluded that the variables of consumer knowledge, service quality, social media marketing and attitudes affect willingness to pay